The Surgical Management of Epilepsy - A Surgeon Perspective (Journal of Fatima Jinnah Medical University, 2024)
Epilepsy is stereotypical clinical manifestation of recurrent, paroxysmal, excessive, synchronous neuronal activity of cerebral cortex. It affects almost 50 million people world wide1 . The incidence of epilepsy is as high as 50- 60 per 100,000. A range of 4 to 10 per 100,000 person per year makes it one of the most prevalent neurological disorder. Its prevalence in Pakistan touches the upper boundary of world’s prevalence, being 9.99 per 1000 people. It is more prevalent in persons younger then 30 years and it is more prevalent in rural areas2.          For a medical personal it may be a clinical scenario but for the affected person it is a big social stigma. Patients suffering from this disease are usually isolated, depressed and deprived of many social rights. Although considered to be disease of high IQ people, every successive fit cause a certain amount of cognitive damage to the affected patient and it can be potentially lethal for the patient and for society if these people have adopted certain professions.          For a county like Pakistan where economy is touching its nadir it is highly difficult for patients to comply with adequate antiepileptic drug (AED) therapy.          One should clearly differentiate between seizure and epilepsy. A seizure is defined as a “Transient occurrence of signs and symptoms due to abnormaly excessive and synchronous neuronal activity in the brain.” For practical purposes epilepsy can be defined as;• At least two un provoked (or reflex) seizures occurring > 24 hours apart.• One unprovoked (or reflex) seizure and probability of further seizures• Diagnosis of an epilepsy syndrome.          Monotherapy is ideal for treatment and control of epilepsy. With increase of number of AEDs the chances of epilepsy control decrease. Surgery is potentially curative for epilepsy or at least it is helpful for reduction of demand of AEDs in carefully selected patients.          International League Against Epilepsy (ILAE) gives its recommendations for selection of surgical candidates.